SPECIFIC FEATURES OF GROUP WORK IN TEACHING ENGLISH (E Conference Zone, 2022)
Group work is when the learners work together on a task or activity in groups. Learners in threes, a class separated into two, and an open class, are all examples of groups. Group work increases the opportunities for all learners to speak the new language.